2011
DOI: 10.1097/olq.0b013e31821b0f50
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness Analysis of Chlamydia trachomatis Screening Via Internet-based Self-collected Swabs Compared With Clinic-based Sample Collection

Abstract: Background Although the Centers for Disease Control and Prevention have recommended population-wide Chlamydia trachomatis screening of sexually active women under 26 years of age, more than half of sexually active young women are not routinely screened. A Website, www.iwantthekit.org (IWTK), was developed in 2004 to promote home-based sample collection. Methods A decision tree was designed to model a hypothetical cohort of 10,000 women per year who order an internet-based Chlamydia trachomatis screening kit.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…10,20 In one, clinician time and STI test costs for clinic screening were compared with test kit, packaging, and postage costs for home screening. 20 Screening rates in the two strategies were assumed to be equal.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…10,20 In one, clinician time and STI test costs for clinic screening were compared with test kit, packaging, and postage costs for home screening. 20 Screening rates in the two strategies were assumed to be equal.…”
Section: Discussionmentioning
confidence: 99%
“…Another study included not only the costs of testing and treatment, but also the theoretical cost savings from prevention of PID. 10 Rates of screening in the internet sampling group were estimated to be higher than in the clinic group based on the authors’ primary data and the literature. The authors concluded that an internet-based self-swab screening strategy led to more PID prevented at a lower cost than clinic screening.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The availability of nucleic acid amplification tests, since the late 1990s, and the ability to test urine and self-collected swabs have made this more feasible. Home-based self-sampling via the internet is acceptable and cost-effective if the return rate is as high as the clinic-based screening rate with 6% positivity 6. It is also convenient and easily accessible.…”
Section: Introductionmentioning
confidence: 99%